2008
DOI: 10.1159/000135515
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel in the Neoadjuvant Treatment for Adeno carcinoma of the Distal Esophagus (AEG I). A Comparison of Two Phase II Trials with Long-Term Follow-Up

Abstract: Introduction: We report a comparative analysis of 2 sequential, prospective phase II trials on the efficacy of platinum/leucovorin/5-fluorouracil (PLF) +/– paclitaxel (T-PLF) in the neoadjuvant treatment of adenocarcinoma of the esophagus (AEG I). Patients and Methods: Inclusion criteria were histologically proven, locally advanced AEG I stage uT3/4 anyN cM0/M1a. 67 patients were treated with either PLF (n = 32) or T-PLF (n = 35). Paclitaxel (80 mg/m2) was added to PLF on days 1, 15, and 29. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…Patients treated additionally with taxanes had the best prognosis, which is in line with literature [13][14][15]. However, in the neoadjuvant setting, no superiority could be shown for taxanes [16], and no randomized data are available so far. The association of merely platinum-based regimens with clinical response might be influenced by the small subgroups, because normally, higher response rates are expected for triple chemotherapy regimens, especially for taxane-containing regimens [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 84%
“…Patients treated additionally with taxanes had the best prognosis, which is in line with literature [13][14][15]. However, in the neoadjuvant setting, no superiority could be shown for taxanes [16], and no randomized data are available so far. The association of merely platinum-based regimens with clinical response might be influenced by the small subgroups, because normally, higher response rates are expected for triple chemotherapy regimens, especially for taxane-containing regimens [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 84%
“…In a study of 802 patients conducted by the MRC in the UK, neoadjuvant chemotherapy with cisplatin and 5-FU significantly improved median OS (16.8 months) compared with surgery alone (13.3 months; p = 0.004) [3]. The median OS of 23 months for all the patients in our analysis compares favorably with the results of the MRC study and a recent German phase II study that reported OS of 18.9 months for a combination of cisplatin and 5-FU, and 43.1 months for a combination of cisplatin, 5-FU, and paclitaxel [13]. In our study, there was no significant difference in median OS between patients with squamous cell carcinoma (28 months for R0 resection and 26 months for R1 resection) and those with adenocarcinoma (23 months for R0 resection and 18 months for R1 resection).…”
Section: Discussionsupporting
confidence: 83%
“…The most common neoadjuvant treatment of esophageal adenocarcinomas at our institution was cisplatin-based chemotherapy (without radiation). 5,14,15 Therefore, patients who were treated with additional radiation for Tumor regression after chemotherapy in esophageal adenocarcinoma exceptional reasons were not included, nor were those with therapy discontinuation before completing one full cycle of chemotherapy included.…”
Section: Discussionmentioning
confidence: 99%